Scheduling linear deteriorating jobs with rejection on a single machine - Cheng, Yushao; Sun, Shijie (European journal of operational research, 2009)
We consider several single machine scheduling problems in which the processing time of a job is a linear function of its starting time and jobs can be rejected by paying penalties. The objectives are to minimize the makespan, the total weighted completion time and the maximum lateness/tardiness plus the total penalty of the rejected jobs. We show that these problems are NP-hard, and design algorithms based on dynamic programming (including pseudo-polynomial time optimal algorithms and fully polynomial time approximation schemes) to solve them.